Management of Amavata w.s.r to Rheumatoid Arthritis-A Case Report - Bano, Shabnam; Dilawer (International Research Journal of Ayurveda & Yoga, 2022)
describes Amavata in detail. Based on clinical similarities, we can compare Amavata to contemporary Rheumatoid Arthritis. Rheumatoid arthritis is the most common chronic inflammatory illness, affecting 0.5 percent of the global population and 0.65 percent to 0.75 percent of the Indian population. Ama dosha interacts directly with Vata dosha in Amavata, causing joint inflammation, deformity, and immobility in the fingers, feet, and ankles, as well as stiffness throughout the body. DMARDs and steroids are used to treat RA, however they do not totally cure disease. Langhana, Swedana, Deepana, Tikta-katu rasa, Virechana, Basti, and other aspects of Amavata management are described in detail in Ayurveda. The 43-year-old female in this case was treated with Ayurvedic drugs. A patient who has been diagnosed is treated with Sinhanad Gugglu, Rasana Saptak Kwath, Sanjivani vati, Ajmodadi churn, and bala Arishta. The end of the treatment contributed to a decrease in overall symptoms.